Fish Cholesterol 25-Hydroxylase Inhibits Virus Replication via Regulating Interferon Immune Response or Affecting Virus Entry - Zhang, Ya; Wang, Liqun; Huang, Xiaohong; Wang, Shaowen; Huang, Youhua; Qin, Qiwei (Frontiers in Immunology, 2019)
Cholesterol 25-hydroxylase (CH25H) is an interferon (IFN)-induced gene that catalyzes the oxidation of cholesterol to 25-hydroxycholesterol (25HC), which exerts broad-spectrum antiviral function. To investigate the roles of fish CH25H in Singapore grouper iridovirus (SGIV) and red-spotted grouper nervous necrosis virus (RGNNV) infection, we cloned and characterized a CH25H homolog from orange-spotted grouper (Epinephelus coioides) (EcCH25H). EcCH25H encoded a 271-amino-acid polypeptide, with 86% and 59% homology with yellow croaker (Larimichthys crocea) and humans, respectively. EcCH25H contained a conserved fatty acid (FA) hydroxylase domain and an ERG3 domain. EcCH25H expression was induced by RGNNV or SGIV infection, lipopolysaccharide (LPS) or poly (I:C) treatment in vitro. Subcellular localization showed that EcCH25H and mutant EcCH25H-M were distributed in the cytoplasm and colocalized partly with the endoplasmic reticulum. SGIV and RGNNV replication was decreased by EcCH25H overexpression, which was reflected in the reduced severity of the cytopathic effect and a decrease in viral gene transcription, but replication of both viruses was increased by knockdown of EcCH25H. Besides, the antiviral activity was dependent on its enzymatic activity. Treatment with 25HC significantly inhibited replication of SGIV and RGNNV. EcCH25H overexpression positively regulated the IFN-related molecules and proinflammatory cytokines, and increased both IFN and ISRE promoter activities. Moreover, EcCH25H overexpression and 25HC treatment significantly suppressed SGIV and RGNNV entry into host cells. Our findings demonstrated that EcCH25H inhibited SGIV and RGNNV infection by regulating IFN signaling molecules, and might also influence viral entry via an effect on cholesterol.